Thermal decomposition of solid benzoyl peroxide using Advanced Reactive System Screening Tool: Effect of concentration, confinement and selected acids and bases. (July 2019) - Shen, Yueqi; Zhu, Wen; Papadaki, Maria; Mannan, M. Sam; Mashuga, Chad V.; Cheng, Zhengdong
Abstract: Benzoyl peroxide (BPO) is one of the most commonly used industrial organic peroxides; however, thermal decomposition of BPO is self-accelerating and can cause fires and explosions; therefore, thermal behavior of BPO decomposition needs to be understood clearly. In this paper, the experimental study of thermal decomposition of solid benzoyl peroxide (BPO) was conducted using the Advanced Reactive System Screening Tool (ARSST). The "onset" temperatures of 75% BPO and 98% BPO were determined to be 98 °C and 79 °C. The confinement tests showed that adding initial pressure can decrease the "onset" temperature, as well as increase the maximum self-heating rate, maximum pressure rise rate, and maximum temperature. Isothermal aging tests were conducted to study the effect of induction. A higher isothermal temperature shortened the induction time. The results showed that BPO can decompose at 75 °C if held at this temperature for a period of time, and the "onset" temperature in isothermal tests can be much lower than that measured in dynamic screening tests. In addition, effect of selected acids and bases on BPO thermal decomposition were investigated. All the additives had little impact on the BPO decomposition reaction under the tested conditions. Further experiments are needed to investigate the thermal hazards of mixtures. Our research is the first in the literature to study BPO decomposition using ARSST and the results provide useful information to characterize hazardous decomposition, and design safe measures during drying, storage, and transportation of BPO. Highlights: The "onset" temperatures of 75% and 98% benzoyl peroxide were determined using the Advanced Reactive System Screening Tool (ARSST). Adding initial pressure can decrease the "onset" temperature, increase the maximum self-heating rate, maximum pressure rise rate, and maximum temperature. Higher isothermal temperature shortened the induction time, and the "onset" temperature in isothermal tests was lower than dynamic screening tests. The selected acids and bases had little impact on the BPO thermal decomposition reaction under the tested conditions.